Metformin Enhances Antidepressant/Antipsychotic Combination Therapy of Schizophrenia With Comorbid Depression in a Murine Model - Zhou, Chunhua; Kong, Dezhi; Xue, Rong; Chen, Min; Li, Gongying; Xu, Yong; Liu, Sha; Tian, Hongjun; Zhuo, Chuanjun (Frontiers in Neuroscience, 2020)
Comorbid depressive disorders confound the diagnosis and therapy of schizophrenia. Using a murine model incorporating both MK801 and chronic unpredictable mild stress exposures, we successfully replicated both psychosis and depression. Ex vivo patch clamp recordings and in vivo calcium imaging demonstrated impaired neural activity in the prefrontal cortex (PFC). We then administered triple-drug combinations consisting of two antidepressants (mirtazapine and venlafaxine) plus an antipsychotic (either clozapine or olanzapine), and found improved PFC neuronal activity and performance in behavioral assays. Moreover, the addition of metformin to both psychotropic drug combinations brought further improvements in depressive and schizophrenic-like behaviors and physiological parameters. In summary, our data modeled the neuropathophysiology of schizophrenia with comorbid depression, and may inform drug intervention strategies.